Evaluation of diffusion-weighted imaging datasets for the assessment of disease activity in lymphoma patients - Haferkamp, Jennifer; Chodyla, Michal-Kamil; Demircioglu, Aydin; Pabst, Kim M.; Jannusch, Kai; Hanoun, Christine; Umutlu, Lale; von Tresckow, Bastian; Schaarschmidt, Benedikt Michael Sebastian; Ludwig, Johannes Maximilian; Grueneisen, Johannes; Milosevic, Aleksandar (European journal of radiology, 2025)
Purpose - To assess the clinical applicability of Diffusion Weighted Imaging (DWI) datasets as a radiation-free alternative to 18F-FDG PET for the evaluation of the vitality of lymphoma lesions. - Material and Methods - A total of 181 patients (mean age: 30.9 ± 19.1 years) with confirmed lymphoma underwent 258 whole-body 18F-FDG PET/MR examinations for primary staging (n = 98), as interim scan during treatment (n = 67), as a follow-up examination (n = 49) or in case of suspected recurrence (n = 44). In each examination, the metabolic activity using standardized uptake values (SUVs) of lymphoma manifestations was measured and disease activity was determined according to the Deauville five-point-scale. In addition, DWI-derived ADC-values as well as the size and volume of the lesions were determined. Correlations between the different quantitative parameters were assessed using Spearman‘s rank test to evaluate the applicability of DWI-data for the discrimination between vital and non-vital lymphoma lesions. - Results - A total of 745 lymphoma manifestations were analyzed, comprising 622 nodal and 123 extranodal lesions. Spearman’s rank correlation revealed a strong/good inverse correlation between the ADCmean (r = 0.83) or ADCmin (0.69) and the SUVs, whereas for the size (r = 0.41) and volume (r = 0.52) a poor/moderate association was found. Furthermore, lymphoma lesions with a Deauville score of 1-3 had significantly higher ADCmean and ADCmin values than lesions with a score of 4-5. ROC-Analysis revealed an area under the curve of 0.95 (ADCmean) or 0.91 (ADCmin) to discriminate lymphoma manifestations with a Deauville-score of 1-3 from lesions with a score of 4 or 5. - Conclusion - The present study demonstrates a strong association between metabolic activity and the cellularity of lymphomas. Furthermore, our results reveal a good performance of DWI-derived ADC values for the differentiation between vital and avital lymphoma lesions. Therefore, DWI-sequences should be considered as a promising radiation-free alternative to FDG-PET, especially for the assessment of indolent lymphoma subtypes with variable FDG-avidity.
Online verfügbar: 16. September 2025, Artikelversion: 18. September 2025
Gesehen am 10.11.2025